Safety and efficacy of l‐histidine monohydrochloride monohydrate produced by fermentation with Escherichia coli (NITE BP‐02526) for all animal species. (8th August 2019) - ,; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on l ‐histidine monohydrochloride monohydrate produced by fermentation with Escherichia coli (NITE BP‐02526) when used as a nutritional additive or as a feed flavouring compound in feed and water for drinking for all animal species. The product under assessment is l ‐histidine HCl H2 O produced by fermentation with a genetically modified strain of E. coli (NITE BP‐02526). The production strain and its recombinant DNA were not detected in the final products. l ‐Histidine HCl H2 O does not give rise to any safety concern to the production strain. The use of l ‐histidine HCl H2 O is safe for the target species when used to supplement the diet in appropriate amounts. It is safe at the proposed use level of 25 mg/kg when used as a flavouring compound for all animal species. The use of l ‐histidine HCl H2 O in animal nutrition raises no safety concerns for consumers of animal products. The additive is not irritating to the skin or eyes and is not a skin sensitiser. There is a risk for persons handling the additive from the exposure to endotoxins by inhalation. The use of l ‐histidine as a feed additive does not represent a risk to the environment. The additive l ‐histidine HCl H2 O is regarded as an effective source of the amino acid l ‐histidine when used as a nutritional additive. For the supplemental l ‐histidine to be as efficacious in ruminants as in non‐ruminant species, it requires protection against degradation in the rumen. It is also considered efficacious as a feed flavouring compound under the proposed conditions of use.